Flow of magnetohydrodynamic viscous fluid by curved configuration with non-linear boundary driven velocity - K.M. Sanni (Taylor & Francis Group, 2021)
This paper discusses the flow of magnetohydrodynamic (MHD) viscous fluid driven by non-linear stretching curved surface. The relevant system of the flow configuration is considered using orthogonal curvilinear geometry in presence of radially varying magnetic field. The governing partial differential equations of the flow problem are reduced into boundary layer regime which are then transformed using similarity variables into ordinary differential equations. The resulting equations of the curved case are not amenable to analytic solutions due to non-linearity of the system. Thus a computational approach through Runge-Kutta fourth order together with the shooting technique is adopted for the numerical solution. The existing solution for flat surface is recovered in validating the present models. The novelty of this work contains the correctness and analytical solution of the existing models over flat surface. The results are interesting and can be useful in polymer dynamics.